INTERPRETATION AND APPLICATION OF INVESTMENT MEASURES IN PRACTICE OF INTERNATIONAL INVESTMENT ARBITRATION - A. A. Danelyan; O. S. Magomedova (Московский журнал международного права, 2019)
INTRODUCTION. Developing States are interested in both the inflow of foreign investment and its efficient use in their national economies. In the furtherance of this objective, host States set in their national legislation trade-related investment measures, referred to as “performance requirements” (requirements to achieve certain national economically useful results). The interests of foreign investors and host States in the matter of measures falling within the concept of “performance requirements” mostly diverge, since these measures create for foreign investors competitive restrictions related to the use of their investments. In legal science and practice there are known trade-related investment measures, such as export requirements, foreign exchange restrictions, local content requirements and others. The possibility for foreign investors to invest without performing trade-related investment measures was one of the main problems of transnational investment. The TRIMs agreement and Art. 1106 of NAFTA are devoted to the sole subject of regulation – “performance requirements”. The idea of limiting these measures was simultaneously discussed in the NAFTA negotiations and within the Uruguay round: the elaborated provisions are similar in some aspects, but have their specific characteristics. The article deals with the rules of both agreements in light of dispute settlement practice. The conclusions of the arbitrators are analyzed in chronological order, which helps to trace the evolution of the single concept in two distinct systems of WTO and NAFTA rules. The article demonstrates the common points and differences in the interpretation of the concerned provisions norms, with consideration for the context and objectives of the agreements. MATERIALS AND METHODS. The materials used in the article include the works of Russian and foreign scholars in the field of international economic law and WTO law, international legal documents adopted within the WTO and NAFTA, as well as materials of judicial and arbitration practice of investment disputes. The research was done on the basis of general and specific scientific methods of cognition (dialectical method, analysis and synthesis, deduction and induction, comparative legal and historical-legal methods). RESEARCH RESULTS. The analysis revealed that trade-related investment measures are part of the “performance requirements” listed in Art. 1106 of NAFTA, which developed countries managed to defend in negotiations with developing countries during the drafting of the TRIMs agreement. Despite the integrity of the concept of “investment requirements”, there is an evident difference in the scope of covered measures, as well as the conceptual difference between the notions of “trims” and “performance requirements”, due to the specifics of the WTO and NAFTA. Nevertheless, in both cases, common qualification criteria of prohibited measures have been developed independently from each other in the practice of investment disputes settlement in order to address similar issues of interpretation. DISCUSSION AND CONCLUSIONS. On the ground of the analysis of arbitration practice in the TRIMs and Art. 1106 of NAFTA, the article gives reasons for the conclusion of the parallel development of the concepts of “trade-related investment measures” and “performance requirements”.